INCLUSIVE LEARNING MANAGEMENT SYSTEM IN KOTA BANJARMASIN KALIMANTAN SELATAN - Muhdi (Pascasarjana Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
This study aims to look at an inclusive learning management system developed in several public and private elementary schools in Banjarmasin. This study is different from other researchers because its achievements are more on how the learning strategy emphasizes the education system for children with special needs and how this achievement can be maximally achieved by looking at comparisons. Although many other researchers also discussed inclusive learning, the strength of this research is the approach taken to see this inclusive education system. The method used in this research is a qualitative field study with a phenomenological approach. The locations studied were several elementary schools in the city of Banjarmasin, South Kalimantan. The results of this study prove that the learning system is more directed at students with various needs as well as the same learning methods as other students, only given special emphasis at special times. This strategy is considered to be able to increase students' confidence in their learning environment. An effective management system is seen from the readiness of the Special Teaching Teachers who understand educational methods for children with special needs, namely the pilot approach. This method is considered effective in the learning and education system in elementary schools for those who need more education than others according to their needs.